Estrategia Digital, Marca Personal de: Natalia Abigail Mejía Moreno - Acosta Quintanilla, Eduardo Ernesto (Universidad de El Salvador. Facultad de Ciencias y Humanidades, 2025)
Disponible en soporte impreso